Creating a Caring Culture: Exploring the Implications of Gratitude in Adult Education - Kellee R. Vess; Jeffrey A. Russell (Adult Education Research Conference, 2014)
Viewing classrooms as a culture, we sought to determine if gratitude could be a meaningful resource for creating a “caring” culture within the classroom setting. Findings suggest that gratitude promotes prosocial behaviors, builds stronger relationships, and helps to develop a greater sense of well-being (McCullough, Emmons, & Tsang, 2002; Emmons, 2008).